Restoration planting options for Pinus flexilis James in the southern Rocky Mountains - Casper, Anne Marie, author; Jacobi, William, advisor; Schoettle, Anna, committee member; Steingraeber, David, committee member (Colorado State University. Libraries, 2012)
Pinus flexilis James populations in the southern Rocky Mountains are severely threatened by the combined impacts of mountain pine beetles and white pine blister rust. P. flexilis' critical role in high elevation ecosystems heightens the importance of mitigating threats to P. flexilis survival. To develop forest-scale planting methods, six P. flexilis seedling planting trial sites were installed, extending from the Medicine Bow National Forest in southern Wyoming to the Great Sand Dunes National Park and Preserve in southern Colorado. Six plots were established at each site, with three plots under areas of high density canopy, and three plots in areas of low density canopy. The following experimental treatments were implemented at each of the six plots: presence/absence of a nurse object and presence/absence of hydrogel. There were six replicates of each treatment combination, with 432 seedlings planted at each of four sites with hydrogel treatment and 216 seedlings planted at each of the two sites without hydrogel treatment, totaling 2,160 seedlings. To determine P. flexilis natural regeneration periodicity and site requirements in surrounding P. flexilis stands, three random plots were installed with five, 4 x 25 m subplots each. In the seedling planting plots, 76% of all planted P. flexilis seedlings were alive three growing seasons after planting. Therefore, data were analyzed comparing healthy trees to those with some degree of foliar damage. When analyzed by orientation to nurse object, there was a higher percentage of healthy trees on the north (77%) and west (78%) side of the nurse object than on the east side (68%) or without an object (63%) (p<0.05). Denser canopy cover was positively correlated with healthier planted seedlings. There was no hydrogel effect for any of the parameters measured. Terminal growth length and needle length were positively correlated with healthy trees. Pith dates from trees in transects within established P. flexilis stands indicate regular recruitment in most decades in the last century. Neither natural regeneration presence nor age was correlated with site characteristics. Density of naturally regenerating seedlings was positively correlated with increasing P. flexilis basal area in the surrounding stand and percent groundcover of trees in the microsite. Presence of natural P. flexilis regeneration in transects was not correlated with planted seedling health. In conclusion, for best growth and survival in the first three years after planting, P. flexilis seedlings should be planted on the north or west side of a nurse object under canopy. However, further data on the effect of canopy cover and object presence on P. flexilis growth is necessary to determine if the impact of canopy and object presence have a negative impact on P. flexilis maturation. Natural regeneration in established P. flexilis stands occurred regularly, and not in infrequent bursts relying on large disturbances.
Keywords: white pine blister rust; five needle pines; tree planting; mountain pine beetle; Cronartium ribicola; Dendroctonus ponderosae